MATHEMATICAL COMMUNICATION SKILLS BASED ON GENDER - Alfarisyi, Dimas; Sutiarso, Sugeng (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
This study was aimed to describe the mathematical communication skill of eighth-grade students of SMP IT Insan Mulia of Batanghari based on gender in solving questions about circle material. The subjects of this study consisted of 21 male and 21 female students. The research method used is descriptive qualitative. The data collection instrument used in this study is the mathematical communication skill test. The mathematical communication skill test instrument consists of three questions in the form of an essay. The results showed that in general, the mathematical communication skills of male and female students are in a low category. The low ability of students' mathematical communication is due to a weak understanding of concepts, not understanding the usefulness of mathematical symbols, and students' unfamiliarity in working on problems. Male and female students have different mathematical communication skills. Female students have better communication skills than male students in conveying ideas to provide an explanation on each indicator of the mathematical communication skills test.